COMMUNICATIVE LANGUAGE TEACHING - Kurbonova Nargiza Samadovna; Tibliyeva Hidoyat Yunusovna (American Journals Publishing, 2024)
Communicative language teaching (CLT), or the communicative approach (CA) , is an approach to language teaching that emphasizes interaction as both the means and the ultimate goal of study.
Keywords: Communicative language teaching, communicative approach, classroom activities, communicative competence.